KERJA SAMA INDONESIA-SINGAPURA DI BIDANG EKONOMI DIGITAL MELALUI PEMBENTUKAN KAWASAN EKONOMI KHUSUS NONGSA DIGITAL PARK DI BATAM (2018-2020) - Varelza Geraldo, (2022)
This research was conducted to determine the realization of the digital economy cooperation agreement between Indonesia and Singapore regarding the Nongsa Digital Park Special Economic Zone in Batam, in this study the author describes how the realization and the opportunities and challenges of the two countries in collaborating in the digital economy sector, as well as outlining the conditions of the digital economy in Indonesia before and after the bilateral cooperation agreement. The research method that the author uses is a qualitative method with a descriptive analysis approach and uses techniques to collect data from primary sources, namely in the form of interviews and secondary data, namely in the form of data obtained through literature studies, in the perspective of international relations, namely with a focus on discussion in the field of bilateral cooperation. The result of this study is an analysis related to the bilateral cooperation agreement between Indonesia and Singapore in the digital economy. Then the effect of the bilateral cooperation between Indonesia and Singapore on the realization of the Nongsa Digital Park Special Economic Zone on Batam Island in March 2018 as a central area for the development of the digital economy in Indonesia.